Quantitative Relation between Coronary Calcium Content and Coronary Flow Reserve as Assessed by Integrated PET-CT Imaging - Curillova, Zelmira (2009)
BACKGROUND: Coronary artery calcium (CAC) is a marker of atherosclerosis. Whether epicardial calcium reflects more widespread atherosclerosis affecting coronary vascular function is unknown. METHODS: We evaluated 136 consecutive patients without known coronary disease (age 62 ±12 years, 68 % females) undergoing vasodilator stress (82)Rb PET and CAC scoring based on clinical grounds. Patients with normal myocardial perfusion on standard semi-quantitative analysis were included. The Agatston CAC score, rest and stress myocardial blood flow (MBF), coronary flow reserve (CFR) and coronary vascular resistance (CVR) were quantified and analyzed on a per patient and per vascular territory basis. RESULTS: Global and regional CAC scores showed modest but significant correlation with hyperemic MBF (r= −0.31 and r= −0.26, p≤0.0002, respectively), CFR (r= −0.28 and r= −0.2, p≤0.001, respectively), and CVR during peak hyperemia (r=0.32 and r= 0.26, p≤0.0002, respectively). There was a modest stepwise decline of mean CFR with increasing CAC score on per patient analysis (1.8 ±0.5 vs 1.7 ±0.5 vs 1.5±0.4, p=0.048 with total CAC= 0, 1-400 and >400 respectively) and per vessel analysis (1.8 ±0.6 vs 1.6 ±0.4 vs 1.5 ±0.5 vs 1.5 ±0.5, p=0.004 with vessel CAC score= 0, 1-100, 101-400 and >400 respectively). In multivariable modeling only body mass index (p=0.005), CAC score (p =0.04) and hypertension (p=0.05) remained predictive. CONCLUSIONS: In patients without overt CAD, there is a modest but statistically significant inverse relationship between CAC content and coronary vasodilator function, which persists after adjusting for the effect of coronary risk factors.